Perceraian dan Solusinya Perspektif Aallamah Kamal Faqih Imani dalam Tafsir Nurul Qur'an - Rusiana, Rusiana Putri; Jubaeli, Ahmad (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2024)
Abstract: The family is the smallest part of society that begins with marriage between a man and a woman. The marriage bond that begins the formation of a family is a sacred bond that is strong in spiritual and social dimensions. This sacred bond is often broken due to problems and pressures within the family. The breaking of this marriage bond is known as divorce. Many things can then lead to this divorce, such as quarrels and disputes, economic factors, domestic violence, infidelity and so on. In Islam itself, divorce is something that is allowed, but it is hated by Allah SWT. In addition, this divorce also has many impacts, both on husbands, wives, each other's families, especially children in the family. Seeing the divorce rate in Indonesia and its impact on many parties, especially children, this divorce can be seen as a problem that needs to be found a solution. In order to find a solution to this divorce problem, the author raises the title Divorce and Its Solution in the Perspective of Allamah Kamal Faqih Imani in Tafsir Nurul Qur'an. The purpose of this study is to find out how Faqih Imani's view in tafsir Nurul Qur'an related to divorce and the solution to this problem. This research uses thematic character and descriptive-analytical methods and uses qualitative research. After conducting research, the author found that in Faqih Imani's view as stated in Tafsir Nurul Qur'an, divorce is a separation between husband and wife caused by two factors including emotional impulses and lust. Meanwhile, the concept of the idah period is a solution so that divorce does not occur, because according to Faqih Imani in Tafsir Nurul Qur'an, wives who are still in their idah period are not allowed to leave their husband's house, with the idah period it is possible that they get the opportunity to evaluate problems or conflicts, misunderstandings, and events that may have triggered problems between the two. So that this idah period becomes a solution or a deterrent to the continuation of the divorce process so that this sacred marriage bond is maintained.